Zhu Shi and Wang Honghan, Pioneers of Integrating Chinese and Western Medicine in the Early Qing Dynasty - Tuo CHEN; Xinzhong YU; Hon Foong Wong; Jin LU (Chinese Medicine and Culture, 2025)
Abstract. When examining the exchange between Chinese and Western medicine during the late Ming and early Qing dynasties, Wang Honghan (王宏翰) stands out as the only Chinese physician who has been thoroughly discussed to date. However, Zhu Shi (祝石) holds a distinct position as the earliest known Chinese to receive Western medical training, extensively practice Western medicine in China, and leave behind medical writings. Drawing on Western anatomical knowledge, Zhu Shi reevaluated traditional Chinese medicine (TCM) and even incorporated distillation techniques into his clinical practice. This paper primarily focuses on Zhu Shi, with comparative reference to Wang Honghan, exploring their medical learning journeys, reflections on TCM, attitudes toward anatomy, Zhu Shi’s influence on Wang Honghan, and their respective medical practices. Through such comparative analysis, this study provides deeper insights into the integration of Chinese and Western medicine during the early Qing dynasty.